Polymer microsphere for profile control and flooding and preparation method thereof

By using the reverse phase emulsion method in the oil field, the problem of poor performance of existing plug-ins under high temperature and high salt conditions was solved, and the effect of efficient sealing and improving crude oil recovery was achieved.

CN119463036AActive Publication Date: 2025-02-18CHINA NAT PETROLEUM CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410082473.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-19
Publication Date
2025-02-18
Estimated Expiration
2044-01-19

AI Technical Summary

Technical Problem

The chemical blocking agent in the existing oilfield has poor performance under high temperature and high salt conditions and cannot effectively seal the high permeability formation, resulting in flooding problems between injection and production wells and reducing crude oil recovery rate.

Method used

The polymer microspheres for driving are prepared by reverse phase emulsion method, and the modified nanocellulose is copolymerized with acrylamide and N-isopropyl acrylamide through TEMPO oxidation to form microspheres with temperature and salt resistance, rigidity and flexibility characteristics. .

Benefits of technology

It has achieved sufficient strength and stability under high temperature and high salt conditions, can penetrate deep into the oil layer, effectively seal the high permeability formation, and improve crude oil recovery rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463036A_ABST
    Figure CN119463036A_ABST
Patent Text Reader

Abstract

The invention provides a polymer microsphere for profile control and flooding and a preparation method thereof. The preparation method comprises the following steps: carrying out TEMPO oxidation modification on nano cellulose, and then preparing a first water-phase mixed solution from the nano cellulose, acrylamide and N-isopropylacrylamide; mixing an oil-phase solvent with an emulsifier to obtain an oil-phase solution; mixing a cross-linking agent, an initiator and the first water-phase mixed solution to obtain a second water-phase mixed solution; dropwise adding the second water-phase mixed solution into the oil-phase solution, stirring at a first rotating speed for a first time, and reacting at a second rotating speed for a second time to obtain a reacted emulsion system; and drying and forming the reacted emulsion system to obtain the polymer microspheres. The polymer microspheres for profile control and flooding are prepared by the preparation method. The polymer microsphere disclosed by the invention is a novel profile control and water plugging agent, has the advantages of good temperature resistance and salt resistance, rigidity, flexibility and the like, can go deep into an oil layer, and has better application in the field of profile control and water plugging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polymer microspheres for adjustment and displacement and a preparation method thereof, belonging to the technical field of oilfield chemistry. Background Art

[0002] In the middle and late stages of oilfield development, due to the existence of formation heterogeneity, the water flooding process in the water injection development process is uneven both in the plane and in the vertical direction. In addition, clay expansion and particle migration and sand removal caused by long-term water flow scouring further lead to the deterioration of heterogeneity. Large or even extra-large pores are formed in some oil layers, causing the high permeability layer between the injection and production wells to be flooded prematurely, reducing the degree of influence of the injected water to the low permeability layer, resulting in the increase of water content in the surrounding oil wells, and even flooding, so that the oil in some low permeability layers cannot be produced. Therefore, in the middle and late stages of oilfield water injection development, oil well water plugging and water injection well profile control, which can plug high permeability formations and increase the swept area, have become important measures to improve crude oil recovery. In addition, with the continuous deepening of oilfield water injection development, the downhole conditions have deteriorated year by year, and many traditional plugging operations have been unable to be realized. In this case, the advantages of chemical plugging are becoming more and more obvious. Therefore, in recent years, the research and application of profile control and water plugging agents have received widespread attention.

[0003] At present, the chemical plugging agents commonly used in oil fields are mainly mobile gels, weak gels, cross-linked polymer coils, etc. formed by cross-linking polymerization of low-concentration partially hydrolyzed polyacrylamide and aluminum citrate under different conditions. However, due to the influence of factors such as high-temperature degradation of polyacrylamide and high-salt high-shear viscosity reduction, the performance of such plugging agents prepared on-site or polymerized downhole is poor under the conditions of oilfield sewage and reservoir temperature, and sometimes even cross-linked polymers cannot be formed. Therefore, it is urgent to develop a plugging agent that can still ensure sufficient strength under high temperature and high salt conditions, is not easy to degrade, and can penetrate deep into the oil layer. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a polymer microsphere for flooding and a preparation method thereof. The polymer microsphere provided by the present invention is a new type of flooding agent, which has the advantages of good temperature and salt resistance, rigidity and flexibility, can penetrate into the oil layer, and can be well applied in the field of profile control and water plugging.

[0005] In order to achieve the above object, the first aspect of the present invention provides a method for preparing polymer microspheres for flooding, which comprises the following steps:

[0006] (1) Preparation of aqueous phase

[0007] The nanocellulose is subjected to TEMPO oxidation modification and then mixed with acrylamide (AM) and N-isopropylacrylamide (NIPAM) to prepare a first aqueous phase mixed solution;

[0008] (2) Oil phase preparation

[0009] mixing the oil phase solvent and the emulsifier to obtain an oil phase solution;

[0010] (3) Synthesis reaction

[0011] Mixing a crosslinking agent and an initiator with the first aqueous phase mixed liquid obtained in step (1) to obtain a second aqueous phase mixed liquid; adding the second aqueous phase mixed liquid dropwise to the oil phase solution obtained in step (2), stirring at a first speed for a first time, and reacting at a second speed for a second time to obtain a reacted emulsion system;

[0012] (4) Drying and molding

[0013] The emulsion system obtained after the reaction in step (3) is dried and formed to obtain the polymer microspheres for flooding.

[0014] In the above preparation method, preferably, step (1) specifically comprises: preparing nanocellulose into a nanocellulose dispersion; mixing a sodium carbonate solution and a sodium bicarbonate solution into a buffer solution; dissolving TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical) and NaBr in the buffer solution, and then mixing with the nanocellulose dispersion under magnetic stirring, and then adding NaClO to carry out an oxidation reaction, during which the pH value of the system is adjusted to 10.0-10.1, and the reaction is terminated after 18 to 24 hours, and the product is washed to obtain a gel-like TEMPO-oxidized modified nanocellulose; preparing the gel-like TEMPO-oxidized modified nanocellulose into a TEMPO-oxidized modified nanocellulose dispersion; mixing the TEMPO-oxidized modified nanocellulose dispersion with water, and ultrasonically vibrating for 10 to 20 minutes to obtain a uniformly dispersed TEMPO-oxidized modified nanocellulose suspension; mixing acrylamide and N-isopropylacrylamide with the TEMPO-oxidized modified nanocellulose suspension to obtain the first aqueous phase mixed solution.

[0015] In the above preparation method, preferably, in step (1), the solid content of the nanocellulose dispersion is 2% to 6%.

[0016] In the above preparation method, in step (1), the concentration and mixing ratio of the sodium carbonate solution and the sodium bicarbonate solution can be conventionally adjusted by a person skilled in the art. For example, the concentrations of the sodium carbonate solution and the sodium bicarbonate solution are 0.1 mol / L respectively, and the mixing volume ratio of the sodium carbonate solution and the sodium bicarbonate solution is 3:2.

[0017] In the above preparation method, preferably, in step (1), the amount of TEMPO used is 0.5% to 1.5% of the mass of the nanocellulose, the amount of NaBr used is 5% to 8% of the mass of the nanocellulose, and the amount of NaClO used is 50% to 80% of the mass of the nanocellulose.

[0018] In the above preparation method, in step (1), the mixing ratio of TEMPO, NaBr, NaClO, buffer and nanocellulose dispersion can be conventionally adjusted by a person skilled in the art based on the above-mentioned ratio range of the present invention. For example, 0.064 g TEMPO and 0.4 g NaBr are dissolved in 50 mL buffer, and then mixed with 300 mL nanocellulose dispersion (solid content is 2%) under magnetic stirring, and then 28 mL NaClO solution (effective chlorine content ≥ 10%) is added.

[0019] In the above preparation method, in step (1), the pH value of the system can be adjusted by using a 2 mol / L sodium hydroxide solution during the oxidation reaction.

[0020] In the above-mentioned preparation method, preferably, in step (1), the mass concentration of the TEMPO oxidized modified nanocellulose dispersion is 10% to 15%.

[0021] In the above-mentioned preparation method, preferably, in step (1), the mixing mass ratio of the TEMPO oxidized modified nanocellulose, the acrylamide and the N-isopropylacrylamide is (1.0-2.0):(0.5-1.5):(0.2-0.5).

[0022] In the above preparation method, preferably, in step (1), the diameter of the nanocellulose is 5 to 70 nm and the length is 100 to 250 nm.

[0023] Nanocellulose (NCC) used in the present invention is a rigid rod-shaped polymer with a diameter of 5 to 70 nm and a length of 100 to 250 nm. It not only has the basic structure and good performance of cellulose, but also has the characteristics of nanoparticles, such as large specific surface area, high elastic modulus and reactivity. In the present invention, before the reaction, the nanocellulose is subjected to TEMPO oxidation modification, and the hydroxymethyl on the surface of the nanocellulose is oxidized to carboxyl groups to increase its water solubility and oxygen barrier properties. A large amount of negative charges are attached to the surface of the nanocellulose after the oxidation modification of the present invention, so that its suspension is more stable, and the long-term stability of the microspheres is improved. Therefore, the present invention adopts TEMPO oxidation-modified nanocellulose as a reinforcing agent for the plugging agent, which significantly improves the thermal stability, long-term stability, mechanical strength, hardness, rigidity and flexibility of the plugging agent.

[0024] In the present invention, N-isopropylacrylamide is introduced into the polymerization monomer. Since the molecule contains hydrophilic amide groups and hydrophobic isopropyl groups, the copolymer prepared by the present invention has a certain thermal sensitivity, and the volume of the copolymer changes with temperature, which is beneficial to improving the blocking ability of the microspheres at high temperatures.

[0025] In the above-mentioned preparation method, preferably, in step (2), the oil phase solvent includes a combination of cyclohexane and chloroform. More preferably, the volume ratio of cyclohexane to chloroform is 4:1 to 5:1. In the technology of preparing polyacrylamide microspheres by inverse emulsion polymerization, vegetable oil is usually used as the oil phase. However, the inventors found that the disadvantage of vegetable oil as the oil phase is that it is easy to chemically react under acidic or alkaline conditions and has a high viscosity. The present invention uses the commonly used organic solvent cyclohexane as the oil phase. However, cyclohexane has poor solubility in the selected Span and Tween series emulsifiers, so the present invention introduces chloroform with a strong polarity and combines it with cyclohexane in a certain proportion to dissolve the emulsifier.

[0026] In the above-mentioned preparation method, preferably, in step (2), the emulsifier includes a combination of Span60 and Tween60. More preferably, the mass ratio of Span60 to Tween60 is 8:1 to 10:1, and further preferably 9:1. Generally speaking, the HLB of the emulsifier is in the range of 3 to 6, and a relatively stable W / O type emulsion can be formed. The present invention most preferably uses a compound of Span60 and Tween60 in a mass ratio of 9:1, and the HLB of the compounded emulsifier is 5.72, which can form a stable W / O type emulsion, which is beneficial to the synthesis of polymer microspheres.

[0027] In the above-mentioned preparation method, preferably, in step (2), the mixing ratio of the emulsifier and the oil phase solvent is (1-2) g:100 mL.

[0028] In the above preparation method, preferably, in step (3), the crosslinking agent includes one or a combination of N,N'-methylenebisacrylamide, N,N'-dicyclohexylcarbodiimide, succinic anhydride and carbodiimide hydrochloride.

[0029] In the above preparation method, preferably, in step (3), the amount of the cross-linking agent used is 4% to 10% of the mass of the TEMPO oxidized modified nanocellulose in the first aqueous phase mixed solution.

[0030] In the above preparation method, preferably, in step (3), the initiator includes one or a combination of ammonium persulfate, benzoyl peroxide, dimethyl sulfoxide and tert-butyl ketone peroxide.

[0031] In the above-mentioned preparation method, preferably, in step (3), the amount of the initiator used is in a mass ratio of (0.1-0.5):(0.5-1.5) to the acrylamide in the first aqueous phase mixture.

[0032] In the above-mentioned preparation method, preferably, in step (3), the volume ratio of the second aqueous phase mixed liquid to the oil phase solution is 1:3 to 1:5. In the present invention, the aqueous phase to oil phase volume ratio (W / O) affects the dispersion of the aqueous phase. If the aqueous phase to oil phase volume ratio is too large, the aqueous phase dispersed droplets in the emulsion will increase, causing the particle size of the synthesized microspheres to become larger, which is prone to precipitation, uneven stirring and other phenomena; if the aqueous phase to oil phase volume ratio is too small, the output of the microspheres will decrease accordingly. At the same time, too low an amount of aqueous phase added is not conducive to the formation of a stable emulsion, affecting the synthesis of the microspheres. The present invention controls the aqueous phase to oil phase volume ratio to 1:3 to 1:5, which can form a stable emulsion and is conducive to the synthesis of microspheres with appropriate particle size and uniform distribution.

[0033] In the above-mentioned preparation method, preferably, in step (3), the second aqueous phase mixed liquid is added dropwise to the oil phase solution obtained in step (2) at a dropping speed of 3 to 5 mL / min.

[0034] In the above preparation method, preferably, in step (3), the first rotation speed is 900-1200 r / min, and the first time is 5-10 min.

[0035] In the above-mentioned preparation method, preferably, in step (3), the second rotation speed is 600-900r / min, the reaction temperature is 50-60°C, and the second time is 2-3h. In the present invention, as the reaction temperature increases, the hydrogen bonds and intermolecular forces between the molecular chains in the TEMPO oxidatively modified nanocellulose particles are continuously weakened, and the surface molecular chains can freely extend into the aqueous solution, thereby increasing the active points of the cross-linking reaction. Moreover, a higher reaction temperature is also conducive to the diffusion of the initiator and the cross-linking agent and the acceleration of the free radical generation rate. However, too high a reaction temperature will also increase the homopolymerization rate of the cross-linking agent, resulting in a decrease in the yield and the degree of cross-linking. The present invention controls the reaction temperature at 50-60°C, which is conducive to the smooth progress of the reaction and makes the reaction degree appropriate, thereby synthesizing polymer microspheres with better performance in all aspects.

[0036] At present, the commonly used methods for synthesizing polymer microspheres include reverse emulsion method, reverse microemulsion method, reverse suspension method, etc. The present invention adopts reverse emulsion method to synthesize polymer microspheres, which has the advantages of simple operation and easy to obtain reaction system.

[0037] In the above-mentioned preparation method, preferably, step (3) further comprises: at the beginning and end of the reaction, taking a small amount of emulsion, dripping it into the water phase and the oil phase respectively, and checking the type of emulsion. Commonly used methods for determining the type of emulsion include the dilution method and the conductivity method. The dilution method is to take two drops of emulsion and drip them into the water phase and the oil phase respectively. The one that can be diluted by the water phase is the water-in-oil (O / W) type, and the one that cannot be diluted by the water phase is the oil-in-oil (W / O) type; the conductivity method is to use a conductivity meter to measure the conductivity of the emulsion. The one with a large conductivity is the water-in-oil (O / W) type, and the one with a small conductivity is the water-in-oil (W / O) type. The present invention adopts the dilution method to determine the type of emulsion, which is simple and intuitive.

[0038] In the above preparation method, preferably, step (4) is to dry and shape the emulsion system after the reaction obtained in step (3) by spray drying to obtain the polymer microspheres for adjustment and displacement. More preferably, step (4) specifically includes: dispersing the emulsion system after the reaction in a first organic solvent, discarding the supernatant, adding a second organic solvent, spraying the obtained solution into an inert gas stream with a sprayer to form small droplets, and then controlling the temperature to remove the first organic solvent and the second organic solvent to obtain the polymer microspheres for adjustment and displacement. Further preferably, the first organic solvent includes anhydrous ethanol; the volume ratio of the first organic solvent to the emulsion system after the reaction is 1:1 to 1:4; the method of dispersing the emulsion system after the reaction in the first organic solvent is magnetic stirring; the second organic solvent includes acetone; the volume ratio of the second organic solvent to the emulsion system after the reaction is 1:1 to 1:4; the temperature for removing the first organic solvent and the second organic solvent is controlled at 20 to 35°C. The present invention uses a spray drying method to dry and shape the microspheres, and uses two organic solvents, which can reduce the surface morphology damage of the microspheres caused by rapid dehydration, and is conducive to obtaining microspheres with complete spherical morphology and uniform particle size distribution.

[0039] In the above preparation method, preferably, in step (4), the particle size of the polymer microspheres for displacement is 50 to 150 μm.

[0040] The second aspect of the present invention provides a polymer microsphere for displacement control, which is prepared by the above-mentioned preparation method.

[0041] According to a specific embodiment of the present invention, preferably, the particle size of the polymer microspheres for flooding is 50 to 150 μm. The polymer microspheres of the present invention can be stored in a dry and sealed state at room temperature.

[0042] The present invention provides a polymer microsphere for flooding and a preparation method thereof. The present invention overcomes the shortcomings of the existing polyacrylamide cross-linked polymer flooding technology. The oil recovery reverse emulsion method of the present invention performs TEMPO oxidation modification on nanocellulose, introduces acrylamide monomer and N-isopropylacrylamide monomer into the TEMPO oxidation modified nanocellulose suspension after ultrasonic vibration, and then adds an initiator and a cross-linking agent, and mixes with the oil phase to form an emulsion under the action of an emulsifier, and copolymerizes the TEMPO oxidation modified nanocellulose, acrylamide monomer, and N-isopropylacrylamide monomer through a cross-linking agent at a certain reaction temperature, and then treats the system after the reaction by spray drying to obtain polymer microspheres, which is a new type of flooding agent.

[0043] As a new type of bio-based functional material, nanocellulose has excellent mechanical properties, huge specific surface area and strong reactivity. A large number of hydroxyl groups are exposed on the surface of cellulose, which makes nanocellulose have great potential for chemical modification. Based on the properties of hydroxyl groups, nanocellulose is subjected to a variety of chemical modifications and various functional groups are grafted to create nanocellulose grafted materials with high strength, high thermal stability and high mechanical properties. However, the current nanocellulose grafted materials may be difficult to meet the needs of oil field profile control and oil recovery. The present invention performs TEMPO oxidation modification on nanocellulose, oxidizing the hydroxymethyl on the surface of nanocellulose to carboxyl groups to increase its water solubility and oxygen barrier properties. The surface of the nanocellulose after oxidation modification of the present invention is attached with a large amount of negative charges, making its suspension more stable, thereby improving the long-term stability of the microsphere plugging agent.

[0044] Polyacrylamide is a water-soluble linear high molecular polymer that can be polymerized into a spatial network structure under appropriate conditions. However, due to the linear characteristics of the molecule itself, polyacrylamide has the ability to change the morphology of the molecular chain, that is, a flexible structure. The flexible structure of polyacrylamide has both advantages and disadvantages in the application process of oil and gas flow control. Flexibility means that the molecule can be deformed and can enter the deep oil layer to achieve deep oil and gas flow control, but it also leads to weak plugging performance, insufficient molecular rigidity, and easy shearing and viscosity reduction.

[0045] The present invention creatively combines TEMPO oxidized modified nanocellulose and acrylamide, and introduces N-isopropyl acrylamide monomer, so that acrylamide monomer, N-isopropyl acrylamide monomer and semi-rigid TEMPO oxidized modified nanocellulose are uniformly mixed in a certain proportion, graft copolymerized in a reverse emulsion system, and dried and formed to obtain polymer microspheres. The present invention controls the mixing ratio of acrylamide, N-isopropyl acrylamide and TEMPO oxidized modified nanocellulose, and by adjusting the ratio of the three within the ratio range controlled by the present invention, polymer microspheres with different particle sizes and strengths can be obtained. The polymer microspheres prepared by the present invention are white powder particles, which are soluble in water when stirred, and the aqueous solution is a white emulsion. The polymer microspheres of the present invention are spherical particles with a particle size of 50 to 150 μm. Experiments show that in the present invention, TEMPO oxidized modified nanocellulose, acrylamide and N-isopropyl acrylamide undergo cross-linking copolymerization, and the microspheres formed by the reaction have a submicron particle size. The introduction of TEMPO oxidized modified nanocellulose makes the microspheres have a certain rigidity, strong plugging performance and long-term stability; the introduction of acrylamide makes the microspheres have a certain elasticity, which can be deformed under the action of pressure difference and penetrate into the main flow channel inside the reservoir; the entry of N-isopropylacrylamide makes the microspheres have a certain thermal sensitivity, and the volume changes with temperature, which is beneficial to improve the plugging ability of the microspheres at high temperature; after the microspheres are broken, nanocellulose crystals can be released, which has a nanoscale effect and can further penetrate into the tiny pores to displace the remaining oil therein.

[0046] The technical solution of the present invention has at least the following beneficial technical effects:

[0047] Compared with the polymer microspheres in the prior art, the polymer microspheres for oil displacement control of the present invention not only have the characteristics of controllable particle size and good uniformity, but also have the advantages of good temperature and salt resistance, wide source of raw materials, and low cost; at the same time, the polymer microspheres have both the rigid characteristics of nanocellulose macromolecules and the flexible and deformable characteristics of acrylamide, and have certain thermal sensitivity; and the polymer microspheres can further penetrate into the oil layer after absorbing water and swelling. The polymer microspheres have certain elasticity and can be deformed under the action of pressure difference and penetrate into the main channel of the reservoir. The volume of the polymer microspheres changes with temperature, which is conducive to improving the plugging ability of the microspheres at high temperature. After the polymer microspheres are broken, nanocellulose crystals can be released, which have a nanoscale effect and can further penetrate into the tiny pores; in addition, the polymer microspheres are not easy to degrade and have strong plugging performance. Based on these advantages, the polymer microspheres for oil displacement control of the present invention can be well applied in the field of profile control and water plugging. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a morphological diagram of the polymer microspheres for flooding prepared in Example 1 in water.

[0049] Figure 2 and Figure 3 This is a morphological diagram of the polymer microspheres for flooding prepared in Example 1 in brine with a mineralization of 4000 mg / L.

[0050] Figure 4 This is the plugging curve of the sand pipe filling experiment with the aqueous solution of polymer microspheres for flooding prepared in Example 1. DETAILED DESCRIPTION

[0051] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0052] In the following embodiments and comparative examples, the experimental raw materials and reagents used mainly include: nanocellulose, TEMPO, NaBr, NaClO, sodium carbonate, sodium bicarbonate, sodium hydroxide, acrylamide, N-isopropylacrylamide, cyclohexane, chloroform, deionized water, N,N'-methylenebisacrylamide (MBAA), Span60, Tween60, ammonium persulfate (APS), etc.; the experimental instruments used mainly include: constant temperature water bath, digital display electric stirrer, constant temperature drying oven, analytical balance, infrared spectrometer, etc.

[0053] Example 1

[0054] (1) Preparation of aqueous phase:

[0055] Deionized water and nanocellulose (diameter 5-70 nm, length 100-250 nm) were used to prepare 300 mL of nanocellulose dispersion with a solid content of 2% for standby use; 0.1 mol / L sodium carbonate solution and 0.1 mol / L sodium bicarbonate solution were mixed in a volume ratio of 3:2 to prepare 200 mL of buffer for standby use; 0.064 g TEMPO and 0.4 g NaBr were weighed and dissolved in 50 mL of buffer, and then poured into 300 mL of nanocellulose dispersion under magnetic stirring, and 2 8mL NaClO solution (effective chlorine content ≥10%), carry out oxidation reaction, during which 2mol / L sodium hydroxide solution is used to adjust the pH value of the system to 10.0-10.1; the reaction is adjusted once every 10 minutes at the beginning of the reaction, and once every 20-30 minutes after 3 hours; the reaction is completed after 18 hours, and the product is filtered and fully washed with deionized water to obtain a gel-like TEMPO oxidized modified nanocellulose, which is transferred to 50mL deionized water to obtain a TEMPO oxidized modified nanocellulose dispersion with a mass concentration of 12%;

[0056] Weigh 1.0 g of TEMPO-oxidized modified nanocellulose dispersion containing 1.0 g of TEMPO-oxidized modified nanocellulose, add an appropriate amount of deionized water, and ultrasonically vibrate for 10 min to obtain a uniformly dispersed TEMPO-oxidized modified nanocellulose suspension; weigh 1.5 g of acrylamide and 0.5 g of N-isopropylacrylamide and add them to the TEMPO-oxidized modified nanocellulose suspension, and ultrasonically vibrate to obtain 20 mL of the first aqueous phase mixed solution;

[0057] (2) Preparation of oil phase: 80 mL of cyclohexane and 20 mL of chloroform were measured, 1.0 g of a composite emulsifier of Span 60 and Tween 60 (the mass ratio of Span 60 to Tween 60 was 9:1) was added, an electric stirring and condensation reflux device was installed, and the mixture was heated and stirred in a constant temperature water bath at 60°C to dissolve the emulsifier, thereby obtaining an oil phase solution;

[0058] (3) Synthesis reaction: weigh 0.1 g of the cross-linking agent MBAA and add it to 20 mL of the first aqueous phase mixture, stir it magnetically to dissolve it, then weigh 0.3 g of the initiator APS and add it to the first aqueous phase mixture, after dissolution, obtain a second aqueous phase mixture; quickly drop the second aqueous phase mixture into the oil phase solution, and drip it within 5 min (the dripping speed is 4 mL / min), first maintain a high-speed stirring speed of 900 r / min for 5 min, then adjust the speed to 600 r / min and react in a constant temperature water bath at 60°C for 2 h to obtain a reacted emulsion system; at the beginning and end of the reaction, use a dropper to take a small amount of the emulsion and drip it into the aqueous phase and the oil phase respectively to check the emulsion type;

[0059] (4) Drying and molding: The emulsion system after the reaction is dried and molded by spray drying. Specifically, after the reaction is completed, the emulsion system after the reaction is poured into a beaker, 30 mL of anhydrous ethanol is added, and magnetic stirring is performed for 0.5 h. The supernatant is discarded, and 30 mL of acetone is added. The obtained solution is sprayed into an inert gas flow by a sprayer to form small droplets, and then the temperature is controlled to room temperature to remove anhydrous ethanol and acetone, and white powder is collected to obtain polymer microspheres for adjustment and flooding.

[0060] The polymer microspheres prepared in this example are white powder particles, which are soluble in water when stirred, and the aqueous solution is a white emulsion. The microspheres in the aqueous solution of the polymer microspheres in this example are observed under an optical microscope. Figure 1 As shown, it can be found that the microspheres are spherical particles with a particle size of about 50 to 150 μm. Adding salt to the polymer microsphere aqueous solution until the mineralization degree is 4000 mg / L, and observing with an optical microscope, it can be found that the salt solution increases the swelling ratio of the microspheres to a certain extent, such as Figure 2 and Figure 3 shown.

[0061] Example 2

[0062] (1) Preparation of aqueous phase: The preparation steps of a 12% TEMPO-oxidized modified nanocellulose dispersion are the same as those in Example 1. Weigh 2.0 g of TEMPO-oxidized modified nanocellulose dispersion, add an appropriate amount of deionized water, and ultrasonically vibrate for 10 min to obtain a uniformly dispersed TEMPO-oxidized modified nanocellulose suspension; weigh 0.5 g of acrylamide and 0.4 g of N-isopropylacrylamide and add them to the TEMPO-oxidized modified nanocellulose suspension, and ultrasonically vibrate to obtain 20 mL of a first aqueous phase mixture;

[0063] (2) Preparation of oil phase: 80 mL of cyclohexane and 20 mL of chloroform were measured, 1.0 g of a composite emulsifier of Span 60 and Tween 60 (the mass ratio of Span 60 to Tween 60 was 9:1) was added, an electric stirring and condensation reflux device was installed, and the mixture was heated and stirred in a constant temperature water bath at 60°C to dissolve the emulsifier, thereby obtaining an oil phase solution;

[0064] (3) Synthesis reaction: weigh 0.2 g of the cross-linking agent MBAA and add it to 20 mL of the first aqueous phase mixture, stir it magnetically to dissolve it, then weigh 0.4 g of the initiator APS and add it to the first aqueous phase mixture, after dissolution, obtain a second aqueous phase mixture; quickly drop the second aqueous phase mixture into the oil phase solution, and drip it within 5 min (the dripping speed is 4 mL / min), first maintain a high-speed stirring speed of 900 r / min for 5 min, then adjust the speed to 600 r / min and react in a constant temperature water bath at 60°C for 2 h to obtain a reacted emulsion system; at the beginning and end of the reaction, use a dropper to take a small amount of the emulsion and drip it into the aqueous phase and the oil phase respectively to check the emulsion type;

[0065] (4) Drying and molding: The emulsion system after the reaction is dried and molded by spray drying. Specifically, after the reaction is completed, the emulsion system after the reaction is poured into a beaker, 30 mL of anhydrous ethanol is added, and magnetic stirring is performed for 0.5 h. The supernatant is discarded, and 30 mL of acetone is added. The obtained solution is sprayed into an inert gas flow by a sprayer to form small droplets, and then the temperature is controlled to room temperature to remove anhydrous ethanol and acetone, and white powder is collected to obtain polymer microspheres for adjustment and flooding.

[0066] Example 3

[0067] (1) Preparation of aqueous phase: The preparation steps of a 12% TEMPO-oxidized modified nanocellulose dispersion are the same as those in Example 1. Weigh 1.5 g of TEMPO-oxidized modified nanocellulose dispersion, add an appropriate amount of deionized water, and ultrasonically vibrate for 10 min to obtain a uniformly dispersed TEMPO-oxidized modified nanocellulose suspension; weigh 1 g of acrylamide and 0.4 g of N-isopropylacrylamide and add them to the TEMPO-oxidized modified nanocellulose suspension. After ultrasonic vibration, 20 mL of the first aqueous phase mixture is obtained;

[0068] (2) Preparation of oil phase: 80 mL of cyclohexane and 20 mL of chloroform were measured, 1.5 g of a composite emulsifier of Span 60 and Tween 60 (the mass ratio of Span 60 to Tween 60 was 9:1) was added, an electric stirring and condensation reflux device was installed, and the mixture was heated and stirred in a constant temperature water bath at 60°C to dissolve the emulsifier, thereby obtaining an oil phase solution;

[0069] (3) Synthesis reaction: weigh 0.15 g of the cross-linking agent MBAA and add it to 20 mL of the first aqueous phase mixture, stir it magnetically to dissolve it, then weigh 0.5 g of the initiator APS and add it to the first aqueous phase mixture, after dissolution, obtain a second aqueous phase mixture; quickly drop the second aqueous phase mixture into the oil phase solution, and drip it within 5 min (the dripping speed is 4 mL / min), first maintain a high-speed stirring speed of 900 r / min for 5 min, then adjust the speed to 600 r / min and react in a constant temperature water bath at 60°C for 3 h to obtain a reacted emulsion system; at the beginning and end of the reaction, use a dropper to take a small amount of the emulsion and drip it into the aqueous phase and the oil phase respectively to check the emulsion type;

[0070] (4) Drying and molding: The emulsion system after the reaction is dried and molded by spray drying. Specifically, after the reaction is completed, the emulsion system after the reaction is poured into a beaker, 30 mL of anhydrous ethanol is added, and magnetic stirring is performed for 0.5 h. The supernatant is discarded, and 30 mL of acetone is added. The obtained solution is sprayed into an inert gas flow by a sprayer to form small droplets, and then the temperature is controlled to room temperature to remove anhydrous ethanol and acetone, and white powder is collected to obtain polymer microspheres for adjustment and flooding.

[0071] Comparative Example 1

[0072] This comparative example is basically the same as Example 1, except that: the nanocellulose is not subjected to TEMPO oxidation modification, a nanocellulose dispersion containing 1.0 g of nanocellulose with a mass concentration of 12% is used, an appropriate amount of deionized water is added, and ultrasonic vibration is performed for 10 minutes to obtain a uniformly dispersed nanocellulose suspension; 1.5 g of acrylamide and 0.5 g of N-isopropylacrylamide are weighed and added to the nanocellulose suspension, and after ultrasonic vibration, 20 mL of the first aqueous phase mixed liquid is obtained; the remaining steps are the same as in Example 1, and polymer microspheres for adjustment and flooding are prepared.

[0073] Comparative Example 2

[0074] This comparative example is basically the same as Example 1, except that N-isopropylacrylamide monomer is not used, and the remaining steps are the same as Example 1 to prepare polymer microspheres for flooding.

[0075] Comparative Example 3

[0076] This comparative example is basically the same as Example 1, except that N-isopropylacrylamide is replaced by acrylic acid, and the amount used is also 0.5 g. The remaining steps are the same as Example 1 to prepare polymer microspheres for flooding.

[0077] Comparative Example 4

[0078] This comparative example is basically the same as Example 1, except that N-isopropylacrylamide is replaced by (3-acrylamidepropyl)trimethylammonium chloride, and the amount used is also 0.5 g. The remaining steps are the same as Example 1 to prepare polymer microspheres for flooding.

[0079] Comparative Example 5

[0080] This comparative example is basically the same as Example 1, except that N-isopropylacrylamide is replaced by dimethylacrylamide, and the amount used is also 0.5 g. The remaining steps are the same as Example 1 to prepare polymer microspheres for displacement.

[0081] Test Example 1

[0082] Physical model experiments were used to evaluate the plugging performance of the polymer microspheres prepared in Examples 1 to 3 and Comparative Examples 1 to 5. A microsphere aqueous solution with a microsphere content of 1000ppm and a mineralization of 4000mg / L was prepared. After sufficient stirring, it was placed in a 45°C thermostat to swell for 24 hours for standby use. Quartz sand of different mesh sizes was selected to fill a 100cm filled sand pipe, which was placed in a 45°C thermostat. The filled sand pipe was flushed with formation water at an appropriate flow rate for 48 hours to simulate the formation of long-term water injection development. The permeability of the sand pipe was measured to be 1.5D. The microsphere aqueous solution was squeezed into the sand pipe at a flow rate of 0.4L / min, and the pressure changes at each pressure measuring point of the sand pipe were recorded.

[0083] The experimental results of Example 1 are as follows Figure 4 As shown, it can be seen that for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the streamline direction rise from 6.8KPa, 5.7KPa, and 5.6KPa to 29.8KPa, 17.3KPa, and 10.5KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops a little. This shows that the aqueous solution containing 1000ppm of polymer microspheres of Example 1 of the present invention can penetrate into the filled sand pipe with a permeability of 1.5D and form a good plugging of the sand pipe, and has good adjustment and displacement performance.

[0084] The experimental results of Example 2 are as follows: for a 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction rise from 7.6KPa, 5.6KPa, and 5.5KPa to 35.4KPa, 15.6KPa, and 8.4KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops a little.

[0085] The experimental results of Example 3 are as follows: for a 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction rise from 5.2KPa, 4.3KPa, and 4.1KPa to 25.3KPa, 19.3KPa, and 12.4KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops a little.

[0086] The experimental results of comparative example 1 are as follows: for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction increase from 5.3KPa, 4.0KPa, and 3.9KPa to 18.3KPa, 11.2KPa, and 6.7KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops slightly.

[0087] The experimental results of comparative example 2 are as follows: for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction increase from 6.6KPa, 5.4KPa, and 5.2KPa to 22.3KPa, 12.4KPa, and 7.7KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops slightly.

[0088] The experimental results of comparative example 3 are as follows: for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction increase from 6.2KPa, 5.2KPa, and 5.1KPa to 26.5KPa, 11.7KPa, and 6.8KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops slightly.

[0089] The experimental results of comparative example 4 are as follows: for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction increase from 5.8KPa, 4.1KPa, and 4.0KPa to 24.3KPa, 10.6KPa, and 5.2KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops slightly.

[0090] The experimental results of comparative example 5 are as follows: for 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the flow line direction increase from 6.8KPa, 5.6KPa, and 5.5KPa to 28.7KPa, 10.7KPa, and 5.6KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops slightly.

[0091] Test Example 2

[0092] A physical model experiment was used to evaluate the heat resistance of the polymer microspheres of Example 1. A microsphere aqueous solution with a microsphere content of 1000ppm and a mineralization of 4000mg / L was prepared. After sufficient stirring, it was placed in a 90°C thermostat to swell for 24 hours for standby use. Quartz sand of different mesh sizes was selected to fill a 100cm filled sand pipe, which was placed in a 90°C thermostat. The filled sand pipe was flushed with formation water at an appropriate flow rate for 48 hours to simulate the formation of long-term water injection development. The permeability of the sand pipe was measured to be 1.5D. The microsphere aqueous solution was squeezed into the sand pipe at a flow rate of 0.4L / min, and the pressure changes at each pressure measuring point of the sand pipe were recorded.

[0093] The experimental results of Example 1 show that for a 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the streamline direction rise from 7.2KPa, 5.9KPa, and 5.8KPa to 31.4KPa, 15.3KPa, and 9.6KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops a little. This shows that the aqueous solution containing 1000ppm of the polymer microspheres of Example 1 of the present invention can still penetrate into the filled sand pipe with a permeability of 1.5D at 90°C and form a good plugging of the sand pipe, and has good temperature resistance.

[0094] Test Example 3

[0095] A physical model experiment was used to evaluate the long-term stability of the polymer microspheres of Example 1. A microsphere aqueous solution with a microsphere content of 1000ppm and a mineralization of 4000mg / L was prepared. After sufficient stirring, it was placed in a 90°C thermostat to swell for 30 days. Quartz sand of different mesh sizes was selected to fill a 100cm filled sand pipe, which was placed in a 90°C thermostat. The filled sand pipe was flushed with formation water at an appropriate flow rate for 48 hours to simulate the formation of long-term water injection development. The permeability of the sand pipe was measured to be 1.5D. The microsphere aqueous solution was squeezed into the sand pipe at a flow rate of 0.4L / min, and the pressure changes at each pressure measuring point of the sand pipe were recorded.

[0096] The experimental results of Example 1 show that for a 1000ppm polymer microsphere solution, as the injection volume increases, the pressure fluctuations at each pressure measuring point of the sand pipe increase; when the injection volume reaches 4.0Vp, the pressures at the three pressure measuring points along the streamline direction rise from 8.5KPa, 6.3KPa, and 6.1KPa to 27.5KPa, 15.4KPa, and 9.5KPa, respectively. After the injection of the microsphere aqueous solution is completed and the formation water is injected, the pressure drops a little. This shows that the aqueous solution containing 1000ppm of the polymer microspheres of Example 1 of the present invention can still have a strong plugging performance when left at 90°C for 30 days, and can deeply fill the sand pipe to form a certain plugging, and has good long-term stability.

[0097] At present, the polymer microspheres prepared by the present invention have been subjected to a plurality of groups of plugging and adjustment and displacement indoor evaluation experiments. The experimental results show that the polymer microspheres of the present invention can form effective plugging and can penetrate deep into the formation. After switching to water drive, they can still maintain a relatively high residual resistance coefficient, can withstand 90°C and have good long-term stability. The polymer microspheres are a better new type of adjustment and displacement plugging material.

Claims

1. A method for preparing polymer microspheres for flooding, comprising the following steps: (1) Preparation of aqueous phase The nanocellulose is subjected to TEMPO oxidation modification and then mixed with acrylamide and N-isopropylacrylamide to prepare a first aqueous phase mixed solution; (2) Oil phase preparation mixing the oil phase solvent and the emulsifier to obtain an oil phase solution; (3) Synthesis reaction Mixing a crosslinking agent and an initiator with the first aqueous phase mixed liquid obtained in step (1) to obtain a second aqueous phase mixed liquid; adding the second aqueous phase mixed liquid dropwise to the oil phase solution obtained in step (2), stirring at a first speed for a first time, and reacting at a second speed for a second time to obtain a reacted emulsion system; (4) Drying and molding The emulsion system obtained after the reaction in step (3) is dried and formed to obtain the polymer microspheres for flooding.

2. The preparation method according to claim 1, wherein The step (1) specifically comprises: preparing nanocellulose into a nanocellulose dispersion; mixing a sodium carbonate solution and a sodium bicarbonate solution into a buffer solution; dissolving TEMPO and NaBr in the buffer solution, and then mixing the buffer solution with the nanocellulose dispersion solution under magnetic stirring, and then adding NaClO to carry out an oxidation reaction, during which the pH value of the system is adjusted to 10.0-10.1, and the reaction is terminated after 18-24 hours, and the product is washed to obtain a gel-like TEMPO-oxidized modified nanocellulose; preparing the gel-like TEMPO-oxidized modified nanocellulose into a TEMPO-oxidized modified nanocellulose dispersion; mixing the TEMPO-oxidized modified nanocellulose dispersion solution with water, and ultrasonically vibrating for 10-20 minutes to obtain a uniformly dispersed TEMPO-oxidized modified nanocellulose suspension; mixing acrylamide and N-isopropylacrylamide with the TEMPO-oxidized modified nanocellulose suspension to obtain the first aqueous phase mixed solution; Preferably, the amount of TEMPO is 0.5% to 1.5% of the mass of the nanocellulose, the amount of NaBr is 5% to 8% of the mass of the nanocellulose, and the amount of NaClO is 50% to 80% of the mass of the nanocellulose; Preferably, the mixing mass ratio of the TEMPO oxidized modified nanocellulose, the acrylamide and the N-isopropylacrylamide is (1.0-2.0):(0.5-1.5):(0.2-0.5).

3. The preparation method according to claim 1, wherein In step (1), the diameter of the nanocellulose is 5 to 70 nm and the length is 100 to 250 nm.

4. The preparation method according to claim 1, wherein In step (2), the oil phase solvent comprises a combination of cyclohexane and chloroform; Preferably, the volume ratio of cyclohexane to chloroform is 4:1 to 5:

1.

5. The preparation method according to claim 1, wherein In step (2), the emulsifier includes a combination of Span60 and Tween60; Preferably, the mass ratio of Span60 to Tween60 is 8:1 to 10:

1.

6. The preparation method according to claim 1, wherein In step (2), the mixing ratio of the emulsifier and the oil phase solvent is (1-2) g:100 mL.

7. The preparation method according to claim 1, wherein In step (3), the cross-linking agent includes one or a combination of N,N'-methylenebisacrylamide, N,N'-dicyclohexylcarbodiimide, succinic anhydride and carbodiimide hydrochloride; Preferably, in step (3), the amount of the cross-linking agent used is 4% to 10% of the mass of the TEMPO oxidized modified nanocellulose in the first aqueous phase mixed solution.

8. The preparation method according to claim 1, wherein In step (3), the initiator includes one or a combination of ammonium persulfate, benzoyl peroxide, dimethyl sulfoxide and tert-butyl ketone peroxide; Preferably, in step (3), the amount of the initiator used is in a mass ratio of (0.1-0.5):(0.5-1.5) to the acrylamide in the first aqueous phase mixture.

9. The preparation method according to claim 1, wherein In step (3), the volume ratio of the second aqueous phase mixture to the oil phase solution is 1:3 to 1:5; Preferably, in step (3), the second aqueous phase mixed solution is added dropwise to the oil phase solution obtained in step (2) at a dropping speed of 3 to 5 mL / min.

10. The preparation method according to claim 1, wherein: In step (3), the first rotation speed is 900-1200 r / min, and the first time is 5-10 min; Preferably, in step (3), the second rotation speed is 600-900 r / min, the reaction temperature is 50-60° C., and the second time is 2-3 h.

11. The preparation method according to claim 1, wherein: Step (4) is to dry and shape the emulsion system obtained after the reaction in step (3) by spray drying to obtain the polymer microspheres for flooding; Preferably, step (4) specifically comprises: dispersing the emulsion system after the reaction in a first organic solvent, discarding the supernatant, adding a second organic solvent, spraying the obtained solution into an inert gas stream with a sprayer to form small droplets, and then controlling the temperature to remove the first organic solvent and the second organic solvent to obtain the polymer microspheres for displacement; More preferably, the first organic solvent includes anhydrous ethanol; the volume ratio of the first organic solvent to the emulsion system after the reaction is 1:1 to 1:4; the emulsion system after the reaction is dispersed in the first organic solvent by magnetic stirring; the second organic solvent includes acetone; the volume ratio of the second organic solvent to the emulsion system after the reaction is 1:1 to 1:4; the temperature for removing the first organic solvent and the second organic solvent is controlled at 20 to 35°C.

12. A polymer microsphere for displacement control, which is prepared by the method for preparing the polymer microsphere for displacement control according to any one of claims 1 to 11; Preferably, the particle size of the polymer microspheres for flooding is 50 to 150 μm.

Citation Information

Patent Citations

  • Nano-crystalline cellulose-based plugging agent and preparation method thereof

    CN110172127A

  • Preparation and application of thermo-sensitive nano-microsphere emulsion and xanthan gum synergistic composite modifying and flooding agent

    CN115746816A

  • Nano polyacrylamide microsphere for profile control based on micro-channel reactor and preparation method of nano polyacrylamide microsphere

    CN116355128A

  • Temperature-resistant and salt-resistant polymer for profile control and flooding as well as preparation method and application of temperature-resistant and salt-resistant polymer

    CN116355131A

  • Environment-friendly high-temperature-resistant and high-salt-resistant filtrate reducer as well as preparation method and application thereof

    CN116836339A